Performance analysis for decision making in team sports - Lorains, M.; Ball, K.; MacMahon, C. (International Journal of Performance Analysis in Sport, 2013)
Decision making is a key aspect of expert performance and is important in many sports. However it has been largely ignored in notational analysis. The aim of this study was to design and test a reliable method of analysing decision-making performance and to use it to evaluate decision making and transfer of training into competition matches. Thirteen elite Australian football (AF) players were analysed over four matches (early season and late season), using a custom-designed decision-making notational analysis system. The performance indicator, decision accuracy, was based on a three-point scale allocated by three elite AF coaches. Other factors measured included number of options available, level of defensive pressure, match context and execution elements. Inter-rater reliability of the notational analysis system was high for all performance indicators (kappa range = .79 - .98). Decision accuracy increased from early to late season while defensive pressure and number of options available for each decision did not differ between games. This research creates an reliable new platform for future research to build upon in order to further develop our ability to measure cognitive skills such as decision making in live match situations, and to also effectively measure transfer of performance gains through off field training interventions